Research on the development of the concept of death in children and its influencing factors - Jingjing, Liu; Fuyan, Liu (Frontiers in Psychology, 2024)
In this study, 114 Chinese children aged 5-6 years old in Henan Province and 114 mothers were selected as research subjects, 59 boys, 55 girls, and 114 mothers. Semi-structured interviews were conducted with children to test the development of the concept of death in children. At the same time, a questionnaire survey was conducted among the children's mothers to analyze the influencing factors of the development of children's concept of death. The results of the study showed that children aged 5-6 yearshad the concept of death, and the sub-components were acquired in a certain order, but the development was not balanced, the overall level of development of the concept of death is slightly higher in girls than in boys; "Whether or not the family talked openly about the topic of death" had a significant effect on the sub-component of the children's concept of death, "Universality of death" (β= -.301, t= -2.007, p<.05) and "Causality of death" (β= .315, t= 2.582, p<.05); and "whether or not there was the experience of exposure to death-related events "had a significant effect on "Irreversibility of death" (β = -.326, t= -2.36, p<.05); Mothers' natural acceptance of death (β= -.293, t= -2.209, p<.05) and convergence-orientated acceptance (β= .415, t= 2.315, p<.05) had significant effects on the " Inorganicity of death" of children's concept of death.